MODERN VIEW ON TREATMENT OF TROPHIC ULCERS - I. L. Mikitin; G. E. Karapetyan; L. V. Kochetova; S. V. Yakimov; R. A. Pakhomova (Креативная хирургия и онкология, 2017)
Article is devoted to one of ancient sections of medicine treatment of wounds. However treatment is long not  healing  wounds and  now remains  to one of important problems of medicine.  Terms of  healing  of  ulcers at  the  majority  of  patients make  2–3  months, at  a number of patients they don’t begin to live for years,  and the  frequency of recurrence at conservative treatment reaches 60–70%. Big prevalence of trophic  ulcers and insufficient efficiency of  existing  conservative methods  of  treatment lead  to  the  huge  economic damage caused  by disability.